Performance of legume mixtures under small-plot periodic grazing - Peters, Michael; Tarawali, Shirley A.; Schultze-Kraft, Rainer; Smith, Jimmy W.; Musa, A. (Wiley, 1999)
The potential of pastures sown with species mixtures of tropical legume species compared with single species was investigated in subhumid west Africa, over a period of three grazing seasons. Through compensation and complementation of the individual legume species, the mixtures were seasonally and temporally (seasonal refers to different seasons in a year, temporal to different years) more stable than the single species stands. Crude protein contents of individual legumes in the mixtures were higher than of the same species grown in signle stands, indicating possible synergistic effects in the mixtures. The ability of legume mixtures to withstand environmental and management variations and thus, their subsequent potential for on-farm utilization under farmers; conditions are discussed.